The Influence of Income, Location, and Motivation on Subsidized Home Purchase Decisions at Adhitama Group in Pekanbaru City - Novelia Henita; Z. Zulkarnain; Gatot Wijayanto (Golden Ratio of Marketing and Applied Psychology of Business, 2026)
One of the government programs and facilities is subsidized housing for people seeking affordable housing, this is a solution for low-income people to have decent housing at affordable prices. This study aims to analyze the effect of income, location, motivation on the decision to purchase subsidized housing at Adhitama Group in Pekanbaru City with a population of 199 subsidized home buyers at Adhitama Group in Pekanbaru City. The determination of the sample refers to Slovin which produces a sample of 133 people using Simple Random Sampling. Data collection using a questionnaire with an ordinal measurement level (Likert scale). The data analysis technique uses Multiple Linear Regression. The validity test uses Pearson correlation product-moment, while the reliability test uses Cronbach Alpha. The results of the hypothesis test of this study indicate that: 1) Income affects the decision to purchase subsidized housing. 2) Location affects the decision to purchase subsidized housing. 3) Motivation affects the decision to purchase subsidized housing. Motivation has the greatest influence on the decision to purchase subsidized housing from other independent variables. 4) Income, location, and motivation influence the decision to purchase subsidized housing, meaning that the higher the consumer's income, strategic location, and consumer motivation, the higher the decision to purchase subsidized housing.